Club Tela: Join the cause, join the club - Buenafe, Patricia Muriel Narciso (Animo Repository, 2022)
The paper presents a report on the business operation of Club Tela, a partnership between six (6) entrepreneurship students from De La Salle University - Manila namely, Regine Piñera, Patricia Buenafe, Carl Ugot, Elliz Mariano, Sara Kim, and Rey Palomo. Club Tela focuses on providing people with canvas goods, a sustainable material that is durable, sturdy, and high-quality, striving to promote a positive mindset through its aesthetic and on-trend designs. In Club Tela, we serve as a voice to raise awareness by providing the essentials. For the business’ first year of operation, Club Tela launched canvas tote bag products with different digitally printed designs which revealed its unique selling point, showcasing artworks that promote saving the environment, self-empowerment, and disco. Furthermore, the report discusses Club Tela’s performance highlights for each functional area namely human resources, information technology, finance, marketing, and production including the attained corporate objective of the business. To support this, Club Tela’s corporate and functional objectives and an evaluation of the established strategies for each functional area were also presented along with the actions taken by the business to overcome challenges that determine its success factors. Following that are significant learnings from the entire business operation, a presentation of the CSR activities, and Club Tela’s plans for the future to conclude the terminal report. Keywords: Club Tela, tote bag, canvas, design, release, e-commerce, social media platforms, Facebook, Instagram, Shopee, Cococart, sustainable, business, start-up, empowerment